Cultural Explanations of Patriarchy, Race, and Everyday Lives: Marginalizing and "Othering" Muslim Women in Canada. Issue 2 (3rd April 2018) - Nagra, Baljit
Abstract: The image of the "oppressed" Muslim woman is one that has become deeply entrenched in Canadian society. It is fuelled not only by the over decade-long "War on Terror", but also by the increasing use of cultural explanations of patriarchy, which posit gender inequalities in Muslim communities as simply being a result of Muslim cultures and religion. While scholars have cited the problems of such an approach, the impact of these representations on Muslim women's everyday lives and their access to important social institutions has not been extensively studied. In a bid to fill this gap, this study draws on 56 in-depth interviews with Canadian Muslim women to illustrate how misperceptions of Muslim women as oppressed and passive victims of their culture and communities works to marginalize and increasingly "other" them in mainstream Canadian society.